Type-2 fuzzy logic based energy-efficient transceiver resource schedule in multi-radio WSNs. (14th October 2019) - Peng, Wei; Chen, Dongyan; Sun, Wenhui; Li, Chengdong; Zhang, Guiqing
Inspired by the type-2 fuzzy logic (T2FL), the energy-efficient radio resource schedule mechanism is proposed to deal with the multi-radio resources management problem in MRWSNs. Firstly, three important models, including channel quality estimation (CQE) model, radio energy dissipation model and residual energy model, are established and analysed. Then using the three important factors as the input variables, the selection probability of each transceiver as output variable, the T2FL based energy-efficient radio resource schedule scheme is designed. Moreover, both experimental and simulation results indicate that the proposed schedule mechanism can effectively improve the network performance, such as throughput, energy efficiency, the success rate of data transmission, etc.